Pendampingan Digital Marketing Pada UMKM Tas Talikur, Kabupaten Blitar, Jawa Timur - Hariyati; Dian Anita Nuswantara; Lintang Venusita (Universitas Negeri Surabaya, 2025)
The PKM activity was carried out in order to help Talikur Bag MSMEs engaged in the field of Talikur Bag Creative Crafts located in Kandangan Village RT 02 and RW 02, Srengat District, Blitar Regency, East Java, become digitally literate MSMEs. In order to have the ability in digital marketing, Talikur Bag business actors in the village must have an understanding, skills and implement sustainable digital marketing which can ultimately increase sales. It is necessary to carry out PKM related to digital marketing to compete in the digital world. Digital Marketing is the key to the success of a business carried out, which in this activity includes promotional activities and seeking market share through digital media by utilizing several digital platforms. This activity was held on May 3, 2024 online at 16.00-18.00 and May 4-5, 2024 offline at: FX Labs Coffee & Eatery, Jl. Ahmad Yani no 121 Blitar starting at: 08.00 - 15.30. This activity was attended by 10 (ten) UMKM. UMKM Talikur Bag actors engaged in the field of Talikur Bag Creative Crafts located in Kandangan Village RT 02 and RW 02, Srengat District, Blitar Regency, East Java. The materials discussed were: Marketing strategies, Creating Digital Marketing content, Digital Marketing as a whole.